Macadamia germplasm and genomic database (MacadamiaGGD): A comprehensive platform for germplasm innovation and functional genomics in Macadamia - Wang, Pan; Mo, Yi; Wang, Yi; Fei, Yuchong; Huang, Jianting; Ni, Jun; Xu, Zeng-Fu (Frontiers in Plant Science, 2022)
As an important nut crop species, macadamia continues to gain increased amounts of attention worldwide. Nevertheless, with the vast increase in macadamia omic data, it is becoming difficult for researchers to effectively process and utilize the information. In this work, we developed the first integrated germplasm and genomic database for macadamia (MacadamiaGGD), which includes five genomes of four species; three chloroplast and mitochondrial genomes; genome annotations; transcriptomic data for three macadamia varieties, germplasm data for four species and 262 main varieties; nine genetic linkage maps; and 35 single-nucleotide polymorphisms (SNPs). The database serves as a valuable collection of simple sequence repeat (SSR) markers, including both markers that are based on macadamia genomic sequences and developed in this study and markers developed previously. MacadamiaGGD is also integrated with multiple bioinformatic tools, such as search, JBrowse, BLAST, primer designer, sequence fetch, enrichment analysis, multiple sequence alignment, genome alignment, and gene homology annotation, which allows users to conveniently analyze their data of interest. MacadamiaGGD is freely available online (http://MacadamiaGGD.net). We believe that the database and additional information of the SSR markers can help scientists better understand the genomic sequence information of macadamia and further facilitate molecular breeding efforts of this species.